1993
DOI: 10.2337/diacare.16.7.1022
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cardiovascular and Renal Complications in Older Adults With Normal or Impaired Glucose Tolerance or NIDDM: A population-based study

Abstract: Prevalent CVD and renal disease were increased in adults with NIDDM and elevated in adults with IGT compared to those with normal glucose tolerance. The prevalence of complications in NIDDM subjects in this population-based study was substantially lower than that reported for clinic-based diabetic populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 4 publications
1
52
1
Order By: Relevance
“…[21][22][23] Moreover, myocardial ischemia due to coronary atherosclerosis commonly occurs without symptoms in patients with diabetes. 29 As a result, multivessel atherosclerosis often is present before ischemic symptoms occur and before treatment is instituted. A delayed recognition of various forms of CHD undoubtedly worsens the prognosis for survival for many diabetic patients.…”
Section: Diabetes and Specific Cvd Atherosclerotic Chdmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23] Moreover, myocardial ischemia due to coronary atherosclerosis commonly occurs without symptoms in patients with diabetes. 29 As a result, multivessel atherosclerosis often is present before ischemic symptoms occur and before treatment is instituted. A delayed recognition of various forms of CHD undoubtedly worsens the prognosis for survival for many diabetic patients.…”
Section: Diabetes and Specific Cvd Atherosclerotic Chdmentioning
confidence: 99%
“…Prospective studies [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] indicate that all of the major cardiovascular risk factors-cigarette smoking, hypertension, and high serum cholesterol-continue to act as independent contributors to CVD in patients with diabetes. As already mentioned, clustering of metabolic risk factors, called the metabolic syndrome, occurs commonly in type 2 diabetes.…”
Section: Covariate Risk Factorsmentioning
confidence: 99%
“…We aimed to include 38 patients in each group to have a 90% probability to detect a true mean difference in the change of LVM index of 15 g/m 2 (assumed s.d., 20 g/m 2 ) and in carotid DC of 2.5 Â 10 À3 /kPa (assumed s.d., 0.8 Â 10 3 /kPa) between the treatment groups at a ¼ 0.05. However, owing to laborious inclusion, we had to stop inclusion before reaching the planned number of patients.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…1,2 Hypertension control in these patients substantially reduces cardiovascular risk, 3 and current guidelines therefore recommend aggressive treatment of hypertension in type II diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…10,[13][14][15] Recently, prediabetic hyperglycemia has been recognized to confer an increased risk for CVD. 16 However, a few population studies 17 have reported a positive association between CVD and impaired fasting glucose (defined as blood glucose of 5.6-6.9 mmol l À1 according to the 2003 American Diabetes Association definition). 18 Evaluation of the combined impact of these two major borderline risk factors is essential in preventing CVD because elevated BP is the highest population attributable fraction (PAF) of CVD incidence, and the incidence of hyperglycemia is increasing in Asian and Western countries.…”
Section: Introductionmentioning
confidence: 99%